2019
DOI: 10.1016/j.watres.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Viability and infectivity of viable but nonculturable Legionella pneumophila strains induced at high temperatures

Abstract: Thermal disinfection is commonly used to prevent the proliferation of culturable Legionella in engineered water systems (EWS). In response to such stress, culturable Legionella populations can switch into a viable but nonculturable (VBNC) state. The importance of such VBNC Legionella cells is currently hotly debated. Here, we investigated the stress response patterns and transitions of the bacteria to the VBNC state at 55°C, 60°C and 70°C on two L. pneumophila strains for >80 days using a combination of cell-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…Warm temperatures, hydrodynamic patterns (specially stagnation) [35], water quality (pH and hardness) [44][45][46][47], corrosion and scaling (as nutrient sources) [48], and surface materials [49,50] have been linked to Legionella prevalence. Additionally, biocidal programs that are not properly set or managed may promote Legionella colonization in several installations [51][52][53][54]. Mimicking the diversity and dynamic conditions of engineered water systems is an unfeasible task in the laboratory.…”
Section: Common Roots Of Research From Legionella Field-based Studiesmentioning
confidence: 99%
“…Warm temperatures, hydrodynamic patterns (specially stagnation) [35], water quality (pH and hardness) [44][45][46][47], corrosion and scaling (as nutrient sources) [48], and surface materials [49,50] have been linked to Legionella prevalence. Additionally, biocidal programs that are not properly set or managed may promote Legionella colonization in several installations [51][52][53][54]. Mimicking the diversity and dynamic conditions of engineered water systems is an unfeasible task in the laboratory.…”
Section: Common Roots Of Research From Legionella Field-based Studiesmentioning
confidence: 99%
“…Most bacteria live in a dynamic environment where the temperature varies, which requires rapid adaptation to stress. Responding to high temperature, many pathogens are known to enter into a viable but non-culturable (VBNC) state, including Escherichia coli (Bruhn-Olszewska et al, 2018), Legionella pneumophila (Cervero-Arago et al, 2019), Listeria monocytogenes (Zolfaghari et al, 2016) and Salmonella typhimurium (Liao et al, 2018). In the VBNC state, cells remain viable but they are no longer culturable with a culturing method but retain certain features of viable cells, such as cellular membrane integrity, metabolic activity and virulence (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, we demonstrated a new data that the Legionella physiological states were not modified by the nebulization process or by its transportation through the 12-stage DLPI or the anatomical model. Thermally or chlorine-induced VBNC Legionella pneumophila may still infect amoebae and pulmonary cells after resuscitation on amoebae (Cervero-Aragó et al, 2019;Epalle et al, 2015;Mustapha et al, 2015). VBNC cell concentrations in the water network must be included in the QMRA models.…”
Section: Discussionmentioning
confidence: 99%